(untitled) (Scientia Agricola, 2017)
Both climatic factors and bee forage characteristics affect the population size and productivity of honey bee colonies. To our knowledge, no scientific investigation has as yet considered the potential effect of nectar-rich bee forage exposed to drastic subtropical weather conditions on the performance of honey bee colonies. This study investigated the performance of the honey bee subspecies Apis mellifera jemenitica Ruttner (Yemeni) and Apis mellifera carnica Pollmann (Carniolan) in weather that was hot and dry and in an environment of nectar-rich flora. The brood production, food storage, bee population and honey yield of Yemeni (native) and Carniolan (imported) colonies on Talh trees (Acacia gerrardii Benth.), a nectar-rich, subtropical, and summer bee forage source in Central Arabia were evaluated. Owing to their structural and behavioral adaptations, the Yemeni bees constructed stronger (high population size) colonies than the Carniolan bees. Although both groups yielded similar amounts of Talh honey, the Yemeni bees consumed their stored honey rapidly if not timely harvested. A. m. jemenitica has a higher performance than A. m. carnica during extremely hot-dry conditions and A. gerrardii nectar-rich flow.